The Impact of Green Technological Innovation and Management Improvement on Environmental Quality in the BRICS Economies - Chishty, Syed Khusro; Rashid, Mohammed; Ansari, Shoaib; Ahmad, Farrukh Rafiq; Mallick, Mohammed Faishal; Khan, Nusrat (International Journal of Energy Economics and Policy, 2025)
This paper proposes a novel framework to analyse the How financial development or management improvement and green technological innovation influence Environmental Quality in BRICS Economies. Using data from 2001 to 2023, the study applies the Westerlund cointegration test to validate the long-term relationship between these variables. Second-generation techniques, including CIPS and CADF stationarity tests, the Pooled Mean Group (PMG) Autoregressive Distributed Lag (ARDL) model, and the Dumitrescu and Hurlin causality analysis, reveal several key findings. Results indicate strong cross-sectional dependence across countries. The PMG estimator demonstrates a significant, negative long-term association between broad money, FDI, green technological innovation, and CO2 emissions, while domestic credit to the private sector shows a positive and significant relationship with carbon emissions. The Dumitrescu and Hurlin causality test identify a non-directional, long-term causality between financial development and CO2 emissions, with unidirectional causality observed between green innovation and carbon emissions. These findings suggest that industrial, financial, and technological advancements are essential for attracting high-quality FDI in BRICS nations; however, they also highlight the adverse environmental impacts of these developments, urging prompt policy responses.